Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

6(2x-3) - 2(2x+1)
can someone get an answer for that ASAP pls
no links :)​


Sagot :

Answer: 8x−20

Step-by-step explanation:

Distribute:

=(6)(2x)+(6)(−3)+(−2)(2x)+(−2)(1)

=12x+−18+−4x+−2

Combine Like Terms:

=12x+−18+−4x+−2

=(12x+−4x)+(−18+−2)

=8x+−20

Answer:

[tex]6 \times 2x = 12x\\ 6 \times - 3 = - 18 \\ - 2 \times 2x = 4x \\ - 2 \times 1 = - 2 \\ now \: add \: like \: terms \\ 12x - 4x = 8x \\ - 18 - 2 = 20 \\ \frac{ - 8x}{8} = \frac{20}{8} \\ x = 2.5 \: or \: \frac{5}{2} [/tex]

Step-by-step explanation:

brainiest please